2008
DOI: 10.1038/sj.ki.5002574
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled study of biocompatible peritoneal dialysis solutions: Effect on residual renal function

Abstract: Residual kidney function is important for patient and technique survival in peritoneal dialysis (PD). Biocompatible dialysis solutions are thought to improve function and viability of peritoneal mesothelial cells and to preserve residual renal function (RRF). We conducted a randomized controlled study comparing use of biocompatible (B) with standard (S) solutions in 93 incident PD patients during a 1-year period. The demographics, comorbidities, and RRF of both groups were similar. At 3 and 12 months, 24-h uri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
121
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(126 citation statements)
references
References 19 publications
2
121
1
2
Order By: Relevance
“…26 Because biocompatible solutions are quite variable with respect to their GDP content, such heterogeneity might explain potentially conflicting trial results. For example, the absence of beneficial effect in the randomized trial by Fan et al 15 could be explained by the fact that 91% of patients in the intervention group received Physioneal, which is reported to contain levels of 3-dexoyglucosone (70-161 mmol/L depending on dialysate glucose concentration 27 ) that are intermediate between those of the intervention group (42-60 mmol/L) and the control group (173-324 mmol/L) in this study. 28 An alternative explanation for a possible renoprotective benefit of biocompatible fluid is reduced peritonitis risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26 Because biocompatible solutions are quite variable with respect to their GDP content, such heterogeneity might explain potentially conflicting trial results. For example, the absence of beneficial effect in the randomized trial by Fan et al 15 could be explained by the fact that 91% of patients in the intervention group received Physioneal, which is reported to contain levels of 3-dexoyglucosone (70-161 mmol/L depending on dialysate glucose concentration 27 ) that are intermediate between those of the intervention group (42-60 mmol/L) and the control group (173-324 mmol/L) in this study. 28 An alternative explanation for a possible renoprotective benefit of biocompatible fluid is reduced peritonitis risk.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a number of randomized controlled trials have not shown any beneficial effect of biocompatible fluids on residual renal function. [15][16][17][18][19] Common features of these trials were that they were underpowered, did not consider nonlinear decline of renal function in their analytic models, and generally enrolled prevalent patients with lower baseline levels of renal function. As with other studies, 22,24 we observed that renal function decline over time was nonlinear, was most marked in the first year of PD, and tended to be slower with biocompatible fluid use in this first year (although not statistically significant).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was also a significant decrease in the levels of circulating AGEs and inflammatory cytokines. In contrast, Fan et al (28) found no difference in PM function between patients using biocompatible solutions (Physioneal or Balance) or conventional dialysis solutions. A recent study by Lee et al (56) also found no significant improvement in PD technique survival with biocompatible solutions.…”
Section: Dialysis Fluids and Pm Integritymentioning
confidence: 94%
“…The BALNET study had longer follow-up compared with the Euro-Balance trial, but baseline rGFR was significantly higher in the group randomized to Balance solution and the study lacked sufficient power to detect a statistically significant difference in RRF between the groups. A recent randomized trial by Fan et al (28) of biocompatible solutions (Physioneal or Balance) versus conventional solutions found no difference in RRF between the groups. Unlike the previous two trials, this trial was powered to detect differences in RRF between the two groups; however, the short follow-up time in this study (9 months) is an important limitation.…”
Section: Dialysis Solutions and Rrfmentioning
confidence: 99%